Adhesive resin composition, adhesive resin layer, metal substrate with adhesive, and laminate
The adhesive resin composition, comprising polyimide resin, maleimide compound, radical initiator, and epoxy resin, addresses the challenge of achieving low dielectric properties and sufficient adhesive strength in high-frequency transmission by optimizing the weight ratios and content levels.
Patent Information
- Application Number
- JP2023170294
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
In high-frequency transmission, metal layers with small surface roughness struggle to achieve sufficient adhesion due to the difficulty in obtaining an anchor effect with adhesives, leading to reduced adhesion to laminated materials.
An adhesive resin composition is developed, comprising a polyimide resin, a maleimide compound, a radical initiator, and an epoxy resin, with specific weight ratios and content levels to achieve low dielectric properties and sufficient adhesive strength.
The adhesive resin composition effectively maintains low dielectric properties in the high-frequency range while ensuring sufficient adhesive strength, even with metal layers having small surface roughness.
Smart Images

Figure 2025059904000007 
Figure 2025059904000008 
Figure 2025059904000009
Abstract
Description
[Technical Field]
[0001] The present invention relates to an adhesive resin composition, an adhesive resin layer, an adhesive-coated metal substrate, and a laminate. [Background technology]
[0002] Circuit boards for high-speed transmission are required to have low dielectric properties (low dielectric constant, low dielectric loss tangent) in the high-frequency range (see, for example, Patent Documents 1 to 7). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 2023-39241 [Patent Document 2] Japanese Patent Publication No. 2023-68801 [Patent Document 3] Japanese Patent Publication No. 2023-75383 [Patent Document 4] Japanese Patent Publication No. 2023-76131 [Patent Document 5] Japanese Patent Publication No. 2023-87152 [Patent Document 6] International Publication No. 2022 / 004583 [Patent Document 7] Patent No. 7287380 Summary of the Invention [Problem to be solved by the invention]
[0004] In high-frequency transmission, metal layers with low surface roughness tend to be used to reduce transmission loss due to the skin effect. If the surface roughness of the metal layer is low, it is difficult to obtain an anchoring effect for adhesives, and adhesion to the laminated material decreases.
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an adhesive resin composition that has low dielectric properties in the high frequency range and can ensure sufficient adhesive strength, as well as an adhesive resin layer, an adhesive-bonded metal substrate, and a laminate that use the adhesive resin composition. [Means for solving the problem]
[0006] The present invention includes the following aspects. An adhesive resin composition according to a first aspect is an adhesive resin composition comprising a polyimide resin (A), a maleimide compound (B), a radical initiator, and an epoxy resin (C), wherein the weight ratio of the polyimide resin (A) to the maleimide compound (B) is 10:1 to 3:2, the content of the radical initiator is 1 part by mass or more and less than 15 parts by mass per 100 parts by mass of the maleimide compound (B), and the content of the epoxy resin (C) is 0.5 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the total of the polyimide resin (A) and the maleimide compound (B), and the adhesive resin composition has a dielectric loss tangent (Df value) in a humidified state of 0.0030 or less, and a difference between the dielectric loss tangent (Df value) in a dry state and the dielectric loss tangent (Df value) in a humidified state of 0.0003 or less, when measured under the following conditions (1) and (2): (1) The dielectric loss tangent (Df value) when dry is measured after the coating has dried, the coating has been further heated to a completely hardened state, the solvent content is reduced to 1 wt% or less, and the coating has been left at 135°C for 1 hour. (2) The dielectric loss tangent (Df value) after humidity control is measured after the coating has dried, and the coating has been further heated to a fully cured state, the solvent content is reduced to 1 wt% or less, and the coating has been left for 24 hours at 23°C and a relative humidity of 50%.
[0007] The adhesive resin layer according to the second embodiment is formed from the adhesive resin composition according to the first embodiment. The adhesive-backed metal substrate according to the third aspect comprises a metal layer on one or both sides of an adhesive resin layer formed from the adhesive resin composition according to the first aspect. A laminate according to a fourth aspect comprises the adhesive-backed metal substrate according to the third aspect on one or both sides of a laminate material. [Effects of the Invention]
[0008] According to the present invention, it is possible to provide an adhesive resin composition that has low dielectric properties in the high frequency range and can ensure sufficient adhesive strength, as well as an adhesive resin layer, an adhesive-coated metal substrate, and a laminate that use the adhesive resin composition. [Brief explanation of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view showing a first example of an adhesive-backed metal substrate. [Figure 2] FIG. 10 is a cross-sectional view showing a second example of an adhesive-backed metal substrate. [Figure 3] FIG. 2 is a cross-sectional view showing a first example of a laminate. [Figure 4] FIG. 10 is a cross-sectional view showing a second example of the laminate. DETAILED DESCRIPTION OF THE INVENTION
[0010] The present invention will be described below based on preferred embodiments.
[0011] The adhesive resin composition according to the embodiment contains a polyimide resin (A), a maleimide compound (B), a radical initiator, and an epoxy resin (C).
[0012] [Polyimide resin (A)] The polyimide resin (A) is not particularly limited, but may be a reaction product of a diamino compound and a tetrabasic acid dianhydride. The polyimide resin (A) may also be chemically modified at least at one end, side chain, or the like. The adhesive resin composition may contain at least one polyimide resin (A), or may contain two or more polyimide resins (A).
[0013] The diamino compound used in the synthesis of the polyimide resin (A) is not particularly limited, but may be an aliphatic or aromatic diamino compound. The aliphatic diamino compound may be one or more of hexamethylenediamine, 1,3-bis(aminomethyl)cyclohexane, and the like. Examples of aromatic diamino compounds include one or more of 9,9-bis(4-aminophenyl)fluorene, 4,4-oxydianiline, 1,3-bis(3-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (also known as 4,4'-(hexafluoroisopropylidene)bis(2-aminophenol)).
[0014] The tetrabasic acid dianhydride used in the synthesis of the polyimide resin (A) is not particularly limited, but examples thereof include one or more of 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, oxydiphthalic anhydride, pyromellitic dianhydride, and the like.
[0015] [Maleimide compound (B)] The maleimide compound (B) is not particularly limited as long as it has one or more maleimide groups in one molecule, but a compound having two or more maleimide groups in one molecule is preferred. The maleimide compound (B) can be obtained by reacting an amino compound having one or more amino groups in one molecule with maleic anhydride. The adhesive resin composition may contain at least one maleimide compound (B), or may contain two or more types.
[0016] Examples of amino compounds used in the synthesis of the maleimide compound (B) include 3,4,4'-triaminodiphenylmethane, triaminophenol, tris-(4-aminophenyl)-phosphate, tris(4-aminophenyl)-phosphate, tris(4-aminophenyl)-thiophosphate, and triethylenetetramine.
[0017] Specific examples of the maleimide compound (B) include trismaleimide compounds such as tris(4-maleimidophenyl)methane, tetramaleimide compounds such as bis(3,4-dimaleimidophenyl)methane, tetramaleimide benzophenone, and tetramaleimide naphthalene, phenol novolac-type maleimide resins, isopropylidenebis(phenoxyphenylmaleimide)phenylmaleimide aralkyl resins, and biphenylene-type phenylmaleimide aralkyl resins.
[0018] [Radical initiator] The maleimide compound (B) is capable of self-crosslinking between maleimide groups due to the action of a radical initiator. This self-crosslinking can improve solder heat resistance. Examples of radical initiators include organic peroxides such as dicumyl peroxide and dibutyl peroxide, and azo compounds such as 2,2'-azobis(isobutyronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile). The adhesive resin composition may contain at least one radical initiator, or may contain two or more radical initiators.
[0019] The content of the radical initiator is from 1 part by mass to less than 15 parts by mass, and more preferably from 3 parts by mass to 10 parts by mass, relative to 100 parts by mass of the maleimide compound (B). When the content of the radical initiator is within the above range, in an adhesive resin composition having low dielectric properties in the high frequency range, it is easy to ensure sufficient adhesive strength even to metal layers used in the high frequency range.
[0020] [Epoxy resin (C)] The epoxy resin (C) is a bifunctional or higher epoxy resin having two or more epoxy groups in one molecule. Specific examples include bisphenol A epoxy resin, bisphenol F epoxy resin, phenol novolac epoxy resin, glycidylamine epoxy resin, naphthalene epoxy resin, glycidyl ether epoxy resin, and phenoxy resin, which is a reaction product of a bisphenol epoxy resin and epichlorohydrin. The adhesive resin composition may contain at least one epoxy resin (C), or may contain two or more epoxy resins.
[0021] The epoxy resin (C) is preferably a low molecular weight compound having a molecular weight of less than 370. The molecular weight of the epoxy resin (C) may be, for example, 200 or more. The epoxy equivalent of the epoxy resin (C) is preferably 160 or less, more preferably 150 or less. The epoxy equivalent of the epoxy resin (C) may be, for example, 90 or more.
[0022] The shortest number of atoms between the two or more epoxy groups contained in the epoxy resin (C) is preferably 9 atoms or less, more preferably 3 atoms or less. The above-mentioned "epoxy group" refers to a three-membered cyclic ether structure (oxirane ring), and the above-mentioned "shortest number of atoms" refers to the number of atoms on the shortest path connecting any two oxirane rings via a covalent bond, excluding the atoms contained in each oxirane ring. Examples of the covalent bond include C-C, C-N, and C-O, but it is preferable that it does not contain a peroxide bond (OO). Furthermore, if a cyclic structure is included on the path, the shortest path within the cyclic structure is selected. If multiple oxirane rings are directly connected by a covalent bond between the carbon atoms C in the ring, the shortest number of atoms is defined as 0. The shortest number of atoms is preferably 1 atom or more, more preferably 3 atoms or more.
[0023] When the epoxy resin (C) is composed of an epoxy compound having a cyclic structure, it is preferably an epoxy resin having one cyclic structure or a structure in which two cyclic structures are linked together. Examples of the cyclic structure include a heterocyclic structure having four or more members or a cyclic hydrocarbon structure. Examples of the heterocyclic structure include a pyridine ring and a thiophene ring. Examples of the cyclic hydrocarbon structure include an alicyclic hydrocarbon structure such as a cyclohexane ring, or an aromatic hydrocarbon structure such as a benzene ring or a naphthalene ring.
[0024] [Adhesive resin composition] In the adhesive resin composition according to the embodiment, the weight ratio of the polyimide resin (A) to the maleimide compound (B) is 10:1 to 3:2, and more preferably 7:1 to 5:2. When the weight ratio is within the above range, the adhesive resin composition has low dielectric properties in the high frequency range, and it is easy to ensure sufficient adhesive strength even to metal layers used in the high frequency range.
[0025] In the adhesive resin composition according to the embodiment, the content of the epoxy resin (C) is 0.5 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass in total of the polyimide resin (A) and the maleimide compound (B). When the content of the epoxy resin (C) is equal to or greater than the lower limit, the epoxy groups that remain after not completely reacting with the polyimide groups of the polyimide resin (A) can chemically bond (e.g., hydrogen bond) with the surface of the metal layer, making it easier to ensure sufficient adhesive strength even for metal layers used in high frequency regions.When the content of the epoxy resin (C) is equal to or less than the upper limit, it makes it easier to ensure sufficient adhesive strength while the adhesive resin composition maintains its low dielectric properties in the high frequency region.
[0026] The adhesive resin composition may contain an organic solvent, such as one or more selected from ester solvents, amide solvents, sulfone solvents, ether solvents, ketone solvents, and aromatic solvents.
[0027] A specific example of the ester solvent is γ-butyrolactone. Specific examples of the amide solvent include N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and N,N-dimethylimidazolidinone. A specific example of the sulfone solvent is tetramethylene sulfone. Specific examples of the ether solvent include diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether monoacetate, and propylene glycol monobutyl ether. Specific examples of ketone solvents include methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone. Specific examples of aromatic solvents include toluene, xylene, and anisole.
[0028] The organic solvent is preferably used in a proportion such that the solids concentration in the adhesive resin composition excluding the organic solvent is generally 10% by mass or more and 80% by mass or less, and more preferably 20% by mass or more and 70% by mass or less.
[0029] The adhesive resin composition can be produced by adding a base agent containing a polyimide resin (A) and a maleimide compound (B) to an organic solvent, and further adding a radical initiator and an epoxy resin (C).
[0030] When measured under the following conditions (1) and (2), the adhesive resin composition according to the embodiment has a dielectric loss tangent (Df value) in a humidified state of 0.0030 or less, and the difference between the dielectric loss tangent (Df value) in a dry state and the dielectric loss tangent (Df value) in a humidified state is 0.0003 or less.
[0031] (1) The dielectric loss tangent (Df value) when dry is measured after the coating has dried, the coating has been further heated to a completely hardened state, the solvent content is reduced to 1 wt% or less, and the coating has been left at 135°C for 1 hour. (2) The dielectric loss tangent (Df value) after humidity control is measured after the coating has dried, and the coating has been further heated to a fully cured state, the solvent content is reduced to 1 wt% or less, and the coating has been left for 24 hours at 23°C and a relative humidity of 50%.
[0032] A completely cured state is, for example, when the degree of cure calculated by DSC measurement (heating rate 10°C / min) = (amount of heat generated before curing - amount of heat generated after curing) / amount of heat generated before curing x 100 (%) is 90% or more. The amount of heat generated before curing is the total amount of heat generated by the sample before curing. The amount of heat generated after curing is the residual amount of heat generated by the cured sample.
[0033] The solvent content can be determined, for example, by TG-DTA measurement (heating rate 10°C / min) as the weight loss when the temperature is raised from 30°C to 250°C. The dielectric loss tangent (Df value) in the dry state may be measured after leaving the sample at 135°C for 1 hour in a state where the solvent content is reduced to 1 wt% or less.
[0034] The dielectric loss tangent (Df value) during humidity conditioning is preferably 0.0023 or less, more preferably 0.0020 or less, and even more preferably less than 0.0020.
[0035] The adhesive resin composition may contain a known additive such as an inorganic filler, etc. Examples of the inorganic filler include, but are not limited to, silica, alumina, calcium carbonate, titanium oxide, glass fiber, and glass powder.
[0036] [Adhesive resin layer] The adhesive resin layer of this embodiment is formed from the adhesive resin composition described above. The adhesive resin layer may be uncured, semi-cured, or fully cured. The adhesive resin layer of this embodiment may be a single-layer adhesive resin layer or a multi-layer adhesive resin layer, and may be a single layer that is not laminated with other layers, or a composite that is laminated with other layers.
[0037] The thickness of the adhesive resin layer is not particularly limited, but is preferably 1 μm or more and 100 μm or less. Specific examples of the thickness of the adhesive resin layer include, but are not particularly limited to, a numerical range having any two upper and lower limit values selected from the group consisting of 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, and 100 μm.
[0038] The adhesive resin layer may contain a material derived from the adhesive resin composition, or may be a composite of a material other than the adhesive resin composition. For example, the adhesive resin layer may contain an inorganic filler and / or glass cloth.
[0039] [Metal substrate with adhesive] The adhesive-backed metal substrate of this embodiment has a metal layer on one or both sides of an adhesive resin layer formed from the adhesive resin composition described above.
[0040] The adhesive-backed metal substrate 21 shown in FIG. 1 has a metal layer 10 on one side of an adhesive resin layer 11 . The adhesive-backed metal substrate 22 shown in FIG. 2 has metal layers 10 on both sides of an adhesive resin layer 11, and is laminated in the order metal layer 10 / adhesive resin layer 11 / metal layer 10.
[0041] The adhesive-backed metal substrates 21 and 22 can be combined with any low-dielectric substrate and thermally laminated to produce circuit boards such as flexible printed circuits (FPCs) and rigid printed circuit boards (PCBs) for high-speed transmission.
[0042] Any suitable conductive material that can be used for circuit boards can be used for the metal layer 10. Specific examples of conductive materials include metals such as copper (Cu), aluminum (Al), iron (Fe), zinc (Zn), and nickel (Ni), as well as alloys containing at least one of these metal elements. Examples of alloys include stainless steel (SUS), steel, and copper alloys.
[0043] Among these, metal foil is preferred as the metal layer 10, and copper foil is more preferred. Rolled copper foil or electrolytic copper foil can be used as the copper foil. The copper foil may be made of pure copper or a copper alloy. Examples of copper alloys include alloys in which trace amounts of tin (Sn), silver (Ag), or the like are added to copper (Cu).
[0044] The metal layer 10 is preferably a metal foil having a surface roughness of 1.5 μm or less. In the case of copper foil, it may be a low-roughening copper foil or a non-roughening copper foil. A low-roughening copper foil is a copper foil having a surface roughness of 1.5 μm or less, more preferably 1.4 μm or less, and particularly preferably 1.3 μm or less. A non-roughening copper foil is a copper foil having a surface roughness of 0.85 μm or less, and may be 0.84 μm or less, or may be 0.82 μm or less. In this specification, surface roughness refers to the ten-point average roughness (RzJIS).
[0045] In this embodiment, even when unroughened copper foil is used as the metal layer 10, an adhesive-coated metal substrate or laminate can be obtained that can ensure sufficient adhesive strength between the laminate material and the metal layer.
[0046] The thickness of the metal layer 10 is not particularly limited, but may be any combination of a lower limit selected from 1.5 μm or more, 3 μm or more, 10 μm or more, etc., and an upper limit selected from 175 μm or less, 100 μm or less, 70 μm or less, etc.
[0047] [Laminate] The laminate of this embodiment has the above-mentioned adhesive-backed metal substrate on one or both sides of the laminate material. The laminate 23 shown in FIG. 3 comprises an adhesive-backed metal substrate 21 on one side of the laminate material 12 . The laminate 24 shown in FIG. 4 includes adhesive-backed metal substrates 21 on both sides of the laminate material 12 .
[0048] The adhesive-coated metal substrate 21 included in the laminates 23, 24 is attached to the laminate material 12 on the side opposite to the side where the adhesive resin layer 11 contacts the metal layer 10, and is laminated in the order of metal layer 10 / adhesive resin layer 11 / laminate material 12, or metal layer 10 / adhesive resin layer 11 / laminate material 12 / adhesive resin layer 11 / metal layer 10.
[0049] The laminating material is not particularly limited as long as it is a material that can be used as a laminate material, and examples thereof include films, sheets, boards, etc. made of resins such as modified polyimide resins, polyester resins, liquid crystal polymers, cyclic olefin resins, polyphenylene ether resins, polyphenylene sulfide resins, polyether ether ketone resins, bismaleimide resins, triazine resins, benzocyclobutene resins, and low dielectric epoxy resins.
[0050] The laminate material may be a prepreg. The prepreg may contain an inorganic filler, may contain both glass cloth and an inorganic filler, or may have a structure in which glass cloth is impregnated with a resin.
[0051] When a polyimide resin film or a modified polyimide resin film is used as the low dielectric substrate, an FPC can be obtained. For example, when a prepreg using polyphenylene ether resin is used as the low dielectric substrate, a rigid substrate can be manufactured.
[0052] In the laminates 23 and 24, the thickness of the adhesive resin layer 11 is preferably 0.5 μm or more and 100 μm or less, and more preferably 1 μm or more and 50 μm or less.
[0053] The thickness of the laminate material 12 is preferably 3 μm or more and 3200 μm or less, and more preferably 10 μm or more and 200 μm or less.
[0054] The thickness of the metal layer 10 is preferably 1.5 μm or more and 175 μm or less, and more preferably 3 μm or more and 70 μm or less.
[0055] When the metal layer 10 is made of a copper layer such as copper foil, the laminates 23 and 24 may be copper clad laminates (CCL).
[0056] The present invention has been described above based on preferred embodiments, but the present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the gist of the present invention. [Example]
[0057] The present invention will be explained in more detail below using examples, but the present invention is not limited to these examples.
[0058] [Preparation of adhesive resin composition] Polyimide resin (A), maleimide compound (B), epoxy resin (C), curing accelerator, and radical initiator were mixed in the proportions shown in the solid content amounts in Tables 1 to 6. In all examples, the proportions of 80 parts by weight of polyimide resin (A), 20 parts by weight of maleimide compound (B), and 1.2 parts by weight of radical initiator were the same, but the proportions of epoxy resin (C) and curing accelerator were changed as shown in Tables 1 to 6. The mixture was diluted with toluene to prepare adhesive resin compositions with solid content concentrations of 40% or 23%.
[0059] [Epoxy resin (C)] In Examples 1-1 and 1-2 shown in Table 1, a tetrafunctional alicyclic glycidylamine type epoxy resin (manufactured by Mitsubishi Gas Chemical Company, Inc., TETRAD (registered trademark)-C, component: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane) was used. In Examples 2-1 to 2-3 shown in Table 2, a tetrafunctional aromatic glycidylamine type epoxy resin (manufactured by Mitsubishi Gas Chemical Company, Inc., TETRAD (registered trademark)-X, component: N,N,N',N'-tetraglycidyl-m-xylylenediamine) was used. In Examples 3-1 to 3-4 shown in Table 3, a bifunctional naphthalene-type epoxy resin (EPICLON (registered trademark) HP-4032D, manufactured by DIC Corporation, component: 1,6-bis(glycidyloxy)naphthalene) was used. In Examples 4-1 to 4-3 shown in Table 4, a trifunctional epoxy resin (manufactured by Mitsubishi Chemical Corporation, jER (registered trademark) 630, component: N,N-diglycidyl-4-(glycidyloxy)aniline) was used. In Examples 5-1 and 5-2 shown in Table 5, a bifunctional aromatic glycidylamine type epoxy resin (GAN, manufactured by Nippon Kayaku Co., Ltd., component: N,N-diglycidylaniline) was used.
[0060] In Comparative Example 1 shown in Table 6, the epoxy resin (C) and the curing accelerator were not used. In Comparative Examples 2-1 and 2-2 shown in Table 6, a bifunctional bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation, jER (registered trademark) 828EL) was used. In Comparative Examples 3-1 and 3-2 shown in Table 6, a trifunctional triphenolmethane type epoxy resin (EPPN-502H, manufactured by Nippon Kayaku Co., Ltd.) was used.
[0061] [Manufacturing adhesive-coated metal substrates] An adhesive resin composition having a solids concentration of 40% for each Example and Comparative Example was applied to an 18 μm thick un-roughened copper foil (Fukuda Metal Foil & Powder Co., Ltd., CF-T9DA-SV) using an applicator so that the adhesive resin layer would be approximately 40 μm thick after drying, and dried at 120° C. to produce adhesive-backed metal substrate 1. Copper foil was then laminated on the resin-coated surface of adhesive-backed metal substrate 1, and the laminate was then laminated at 200° C. for 60 minutes at 3 MPa to produce adhesive-backed metal substrate 2 (Cu / Ad / Cu).
[0062] [Laminate manufacturing] An adhesive resin composition with a solids concentration of 23% for each Example and Comparative Example was applied to an 18 μm thick unroughened copper foil (Fukuda Metal Foil & Powder Co., Ltd., CF-T9DA-SV) using a bar coater so that the adhesive resin layer would be 3 μm thick after drying, and then dried at 120°C to produce two sets of adhesive-backed metal substrates with identical specifications. These adhesive-backed metal substrates were laminated in the following order: copper foil / adhesive resin layer / prepreg / adhesive resin layer / copper foil, and laminated at 195°C for 100 minutes at 3.0 MPa to produce a laminate (double-sided CCL). Panasonic's MEGTRON® 6 prepreg was used.
[0063] [Measurement of dielectric loss tangent (Df value)] The obtained adhesive-attached metal substrate 1 was cured under vacuum conditions at 200°C for 60 minutes. The copper foil was then removed by etching, and the dielectric loss tangent (Df value) in the dry state and the dielectric loss tangent (Df value) in the humidified state were measured at a frequency of 10 GHz using a dielectric constant measuring device (cavity resonator type, manufactured by ATE) according to the above conditions (1) and (2).
[0064] [Solder heat resistance test] The adhesive-backed metal substrate and laminate (double-sided CCL) of each example and comparative example were dried at 135°C for 1 hour, then floated in a solder bath at 288°C, and the time until deformation or bubbling occurred was measured to evaluate heat resistance. If no deformation or bubbling occurred after 600 seconds, it was rated as passing.
[0065] [Peel adhesion strength of adhesive-backed metal substrate 2 (Cu / Ad / Cu)] The adhesive strength between the copper foils of the resulting adhesive-coated metal substrate 2 (Cu / Ad / Cu) was measured. The obtained adhesive-attached metal substrate 2 (Cu / Ad / Cu) was cut to a width of 10 mm to obtain a test piece. One copper foil portion was attached to a ring core with a diameter of 11 cm, and the other copper foil portion was pulled at a speed of 50 mm / min, thereby conducting a 90° peel test. As an index of adhesive strength between copper foils, a passing value was 0.85 N / mm or more.
[0066] [Peel adhesion strength of laminate (double-sided CCL)] The adhesive strength between the copper foil and the prepreg of the obtained laminate (double-sided CCL) was measured. The resulting laminate (double-sided CCL) was cut into a width of 10 mm to obtain a test piece. The prepreg side was attached to a ring core with a diameter of 11 cm, and a 90° peel test was performed by pulling the copper foil portion at a speed of 50 mm / min. As an index of adhesive strength between copper foil and prepreg, a passing value was 0.53 N / mm or more.
[0067] The results are shown in Tables 1 to 6.
[0068] [Table 1]
[0069] [Table 2]
[0070] [Table 3]
[0071] [Table 4]
[0072] [Table 5]
[0073] [Table 6]
[0074] According to the adhesive resin composition of the example, an adhesive resin layer was obtained in which the dielectric loss tangent (Df value) when conditioned was 0.0030 or less and the difference between the dielectric loss tangent (Df value) when dry and the dielectric loss tangent (Df value) when conditioned was 0.0003 or less. [Explanation of symbols]
[0075] 10...metal layer, 11...adhesive resin layer, 12...laminate material, 21, 22...adhesive-coated metal substrate, 23, 24...laminate
Claims
1. An adhesive resin composition comprising a polyimide resin (A), a maleimide compound (B), a radical initiator, and an epoxy resin (C), the weight ratio of the polyimide resin (A) to the maleimide compound (B) is 10:1 to 3:2; the content of the radical initiator relative to 100 parts by mass of the maleimide compound (B) is 1 part by mass or more and less than 15 parts by mass, a content of the epoxy resin (C) is 0.5 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass in total of the polyimide resin (A) and the maleimide compound (B), The adhesive resin composition is characterized in that, when measured under the following conditions (1) and (2), the dielectric dissipation factor (Df value) in a humidified state is 0.0030 or less, and the difference between the dielectric dissipation factor (Df value) in a dry state and the dielectric dissipation factor (Df value) in a humidified state is 0.0003 or less. (1) The dielectric tangent (Df value) in a dry state is measured after the coating and drying, the coating is further heated to a completely cured state, the solvent content is reduced to 1 wt % or less, and the coating is left at 135° C. for 1 hour. (2) The dielectric tangent (Df value) after humidity control is measured after the coating and drying, the coating is further heated to a completely cured state, the solvent content is reduced to 1 wt % or less, and the coating is left to stand for 24 hours under conditions of 23°C and a relative humidity of 50%.
2. An adhesive resin layer formed from the adhesive resin composition according to claim 1.
3. 2. An adhesive-coated metal substrate comprising an adhesive resin layer formed from the adhesive resin composition according to claim 1 and a metal layer on one or both sides of the adhesive resin layer.
4. A laminate comprising the adhesive-backed metal substrate according to claim 3 on one or both sides of a laminate material.
Citation Information
Patent Citations
Polyimide resin, resin composition containing the polyimide resin and cured product of the same
JP2023039241A
Polyimide resin composition and cured product of the same
JP2023068801A
Polyimide resin composition and cured body thereof
JP2023075383A
Polyimide resin, resin composition containing the polyimide resin and cured product of the same
JP2023076131A
Polyimide resin, resin composition comprising polyimide resin and cured product thereof
JP2023087152A